More Gender Equality, More Homogamy? A Cohort Comparison in Six European Countries - Falcon Julie; Joye Dominique (Swiss Journal of Sociology)
We study whether educational homogamy has increased following the rise of women’s educational attainment and of egalitarian couples in France, Germany, the Netherlands, Spain, Switzerland and the United Kingdom. From the analysis of data from the European Union and Swiss Labour Force Surveys over a 15-year period (1999–2013), we observe that educational homogamy did not increase across cohorts, although we find substantial differences in the degree of homogamy according to couple arrangements.